The Neural Correlates of Face-Voice-Integration in Social Anxiety Disorder - Kreifelts, Benjamin; Ethofer, Thomas; Wiegand, Ariane; Brück, Carolin; Wächter, Sarah; Erb, Michael; Lotze, Martin; Wildgruber, Dirk (Frontiers in Psychiatry, 2020)
Faces and voices are very important sources of threat in social anxiety disorder (SAD), a common psychiatric disorder where core elements are fears of social exclusion and negative evaluation. Previous research in social anxiety evidenced increased cerebral responses to negative facial or vocal expressions and also generally increased cerebral sensitivity to voices and faces. But it is unclear if also the cerebral process of face-voice-integration is altered in SAD. Applying functional magnetic resonance imaging, we investigated the correlates of the audiovisual integration of dynamic faces and voices in SAD as compared to healthy individuals. In the bilateral midsections of the superior temporal sulcus (STS) increased integration effects in SAD were observed driven by greater activation increases during audiovisual stimulation as compared to auditory stimulation. This effect was accompanied by increased functional connectivity with the visual association cortex and a more anterior position of the individual integration maxima along the STS in SAD. These findings demonstrate that the audiovisual integration of facial and vocal cues in SAD is not only systematically altered with regard to intensity and connectivity but also the individual location of the integration areas within the STS. These combined findings offer a novel perspective on the neuronal representation of social signal processing in individuals suffering from SAD.